The Influence of Islamic Corporate Governance Towards Financial Performance (Empirical Study on Sharia Commercial Banks in Indonesia Year 2013-2017) - Nursaidah Nasution; Nasrizal Nasrizal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This study aims to find empirical evidence of the Islamic corporate governance mechanism influence the institutional ownership, commissioner board proportion, a board of independent commissioners, the sharia supervisory board proportion, and the audit committee on financial performance. The population of this study is Sharia Commercial Bank in Indonesia year 2013-2017. The population is 13 Sharia Commercial Banks. The sampling technique in this study used a purposive sampling technique. This study obtained 9 banks. The data used is secondary data and data analysis methods using multiple regression analysis. The result of this study concludes that the institutional ownership, the size of board commissioners, independent commissioner board, the size of the sharia supervisory board, and the audit committee do not affect financial performance.